Bacterial detection with amphiphilic carbon dots1. Issue 12 (21st June 2015) - Nandi, Sukhendu; Ritenberg, Margarita; Jelinek, Raz
<x xml:space="preserve">Abstract</x> Amphiphilic carbon dots employed for detection and visualization of bacterial cells and distinguishing among different bacterial strains.